Determinants of Nutritional Status, Weight Gain, and Utilization of Health Services in Toddlers: A Literatur Review - Babby Ika Pratiwi; Syahrial Syahrial; Frima Elda (GLOBAL HEALTH SCIENCE GROUP, 2026)
Nutritional problems in toddlers, such as stunting and underweight , as well as non-compliance in growth and development monitoring remain major public health challenges. Participation in health services such as Posyandu and other determinants that influence nutritional status need to be identified more deeply to determine appropriate interventions. This study aims to synthesize current research on the determinants of nutritional status, successful weight gain, and factors that influence the utilization of toddler health services. The method used is a literature review by searching for articles online through the Google Scholar database (13,430 articles), ScienceDirect (6,674 articles), and PubMed (499 articles). The article search used the keywords